Efficacy and safety of Nefecon in IgA nephropathy: real world clinical practice - Zhai, Zihan; Huang, Zhibin; Wang, Liuwei; Yu, Lu; Gou, Rong; Wang, Yulin; Li, Qiuhong; Guo, Yanhong; Tang, Lin (Frontiers in Immunology, 2026)
IntroductionThe targeted-release budesonide formulation (Nefecon) addresses IgA nephropathy (IgAN) by inhibiting mucosal immune dysregulation in gut-associated lymphoid tissue (GALT), leading to reduced production of galactose-deficient IgA1 (Gd-IgA1). Randomized controlled trials (NEFIGAN, NefIgArd) have shown that Nefecon effectively decreases proteinuria and decelerates the progression of chronic kidney disease (CKD) in patients with IgA nephropathy (IgAN). However, evidence in real-world clinical settings and high-risk subgroups remains limited.MethodsWe performed a retrospective cohort study involving 60 IgAN patients treated with Nefecon (16 mg/day) for no less than 6 months at the First Affiliated Hospital of Zhengzhou University between October 2024 and November 2025. The study focused on evaluating alterations in proteinuria and estimated glomerular filtration rate (eGFR). Subgroup analyses were further carried out according to the use of concomitant immunosuppressive therapy, baseline proteinuria levels, and baseline renal function.ResultsProteinuria decreased significantly after 4 and 6 months of Nefecon treatment (median reduction 31.9% and 43.5%, respectively; both p < 0.001), while eGFR remained stable. Patients receiving Nefecon plus glucocorticoid/immunosuppressive therapy achieved greater proteinuria reduction than those on Nefecon monotherapy (48.1% vs. 35.8% at 6 months, p=0.04). Notably, patients with a baseline eGFR < 35 mL/min/1.73 m² showed a 38.9% reduction in proteinuria (p=0.002) without additional renal deterioration. Nefecon was well tolerated, with adverse events being mild.ConclusionIn routine clinical practice, Nefecon effectively reduces proteinuria and preserves renal function in IgAN, even in patients excluded from randomized trials. The combination with immunosuppressive therapy may provide additive benefit that requires further validation. These findings extend trial results to real-world settings and highlight Nefecon as a practical treatment option for high-risk IgAN patients.